Impact of Ultrasound-Guided Deep Serratus Anterior Plane Block Combined With Dexmedetomidine as an Adjuvant to Ropivacaine Inpatient Quality of Recovery Scores Undergoing Modified Radical Mastectomy: A Randomized Controlled Trial - Wu, Yu; Kang, Yuling; Li, Yanli; Fu, Bohan (Frontiers in Oncology, 2022)
Background Breast cancer has overtaken lung cancer as the most commonly diagnosed malignancy and is the leading cause of cancer-related death in women. Surgery is the only possible cure for breast cancer, and the incidence of acute postoperative pain (APP) is high in breast surgery. Previous reports suggested that ultrasound-guided deep serratus anterior plane block (dSAPB) provided effective blockade to relieve pain after modified radical mastectomy for breast cancer. In fact, despite the long-acting local anesthetic agents used, the patient’s pain cannot completely be eliminated due to the short duration of anesthesia. Dexmedetomidine as an adjunct to local anesthetics can prolong peripheral nerve block duration. However, no study has investigated the role of dSAPB with dexmedetomidine in the quality of recovery scores undergoing modified radical mastectomy. Thus, this study was conducted aiming at this aspect. Material and Methods This single-center, double-blind, randomized clinical trial was conducted at Bethune International Peace Hospital. A total of 88 participants of elective modified radical mastectomy were enrolled from May and November 2021. Ultrasound-guided dSAPB combined with 30 ml of 0.375% ropivacaine or 30 ml of 0.375% ropivacaine with dexmedetomidine (1 μg/kg) was administrated before anesthesia at the fourth to fifth ribs of the axillary midline. The primary outcome was quality of recovery, measured 24 h postoperatively using the QoR-15. Secondary outcomes were the Visual Analogue Scale (VAS) scores at rest and movement at 1, 6, 12, 24, and 48 h after surgery, 48 h sufentanil consumption postoperatively, the incidence of postoperative nausea and vomiting (PONV), length of post-anesthesia care unit (PACU) stay, dizziness, delirium, SAPB-related adverse events, and patient’s satisfaction with pain management. Results Among the 88 participants, 8 did not meet the inclusion criteria; the other 80 were randomized to receive dSAPB combined with ropivacaine (Group R, N=40) and dSAPB combined with ropivacaine plus DEX (Group RD, N=40), of which a total of 7 (4 in Group R and 3 in Group RD) were excluded due to protocol deviation. Eventually,73 participants (36 in Group R and 37 in Group RD) were included for final analysis, with age (SD, years, 54.08[6.28] vs. 54.62[7.44], p=0.740), body mass index (BMI) (SD, 27.96[1.67] vs. 27.57[2.38], p=0.428), and median preoperative global QoR-15 score (interquartile range (IQR), 127[123.25–131] vs. 126[121–130], p=0.662). The median postoperative global QoR-15 score (IQR, 107[103–112] vs. 109.5[107–114], p=0.016), VAS score at rest at 12th hour (IQR, 1[1–2] vs. 1[1–2], p=0.033), VAS score in movement at 12th hour (IQR, 2[1–3] vs. 2[1–3], p=0.014) and at 24th hour (IQR, 3[2–3] vs. 3[2–3], p=0.040), and median sufentanil rescues consumption (IQR, 14[12–17 vs. 14[12–15], p=0.022] of Group RD were significantly lower than those of the Group R. Patient satisfaction score (SD, 8.28[0.70] vs. 8.62[0.59], p=0.024) of Group RD were significantly higher than those of the Group R. Conclusion The ultrasound-guided dSAPB combined with dexmedetomidine plus ropivacaine may improve the QoR-15 in patients undergoing modified radical mastectomy and indicates that it may be a useful intervention to aid recovery following breast cancer surgery. Furthermore, participants in the ropivacaine with DEX group met the superior pain relief in the early postoperative period, reduced postoperative cumulative opioid consumption, increased patient satisfaction, and no increase in the incidence of complications.